Analysis Of Project Success Inhibition Factors - Zulyaden, Zulyaden; Rinaldy, Rinaldy (Department of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2021)
In the implementation of activities we often find what is called a project. The project is an activity that must be completed in accordance with the specified target and time, so that the project can be regarded as a success in project implementation. One of the projects in ques-tion is the construction project. Construction projects in their implementation we often encounter various kinds of problems that arise from the elements involved in them, so this can hamper the success of a project that is being implemented. One problem that arises from the contractor factor and contract specification. The purpose of this study is to find out one of the main inhibiting factors in the successful implementation of construction projects in Aceh Province. Classification of construction services for respondents is all construction ser-vices from the middle class (M) to large classes (B). The data obtained the total population of construction services as many as 508 con-tactors from observations of projects that have been completed from 2010-2015 with funds from the Aceh Budget (APBA). By using the Slovin formula a total sample of 84 contractors was found. The method used in this study is a combined method, namely qualitative and quantitative methods through questionnaires. The independent variables reviewed are the contractor factor and the contract specification factor while the dependent variable is the success of the project. For statistical analysis the data process is done by using validity and reliability tests, while analyzing the data is done by using multiple linear regression with the help of Product Solution and Service Statis-tics (SPSS) version 22. The results of the study indicate that the contractor factor is one of the main inhibiting factors in the successful implementation of the project in Aceh Province.